Changes in knowledge of safe sex and sexual behaviour among male vocational high school students in Zhejiang Province, China: a 6-year cross-sectional comparison (2015–2021) - Wang, Hui; Ma, Qiaoqin; He, Lin; Jiang, Tingting; Chen, Wanjun; Zhen, Jinglei; Chen, Weiyong (Frontiers in Reproductive Health, 2025)
BackgroundVocational high school students in China exhibit higher rates of sexual activity than their academic counterparts; however, existing studies predominantly focus on college populations, leaving a critical gap in longitudinal data tracking the evolution of sexual knowledge and behavioural patterns among vocational students. This study aimed to evaluate changes over time in sexual safety knowledge, STIs/HIV and reproductive health-related sexual behaviours among boys who have had sex in Chinese vocational high schools.MethodsIn 2015 and 2021, an anonymous survey was conducted separately using the same questionnaire and survey method among students in Years 1–2 of the same vocational high school in a district of Zhejiang Province. The results of the two surveys were compared using univariate analyses, and multivariate analyses.ResultsIn 2015 and 2021, 180 and 90 male students, respectively, had ever had sex, representing rates of 17.44% (180/1,032) and 8.49%(90/1,060). The results of the multivariate analysis showed that, in 2021, those who knew that sexual contact was the main mode of HIV transmission(OR = 14.14, 95% CI: 7.16–27.92), knew that contracting an STI increased the likelihood of HIV infection (OR = 7.83, 95% CI: 4.30–14.29), and knew that condom use could reduce both STIs(OR = 33.51, 95% CI: 15.08–74.49) and HIV infection(OR = 16.77, 95% CI: 8.58–32.76) were significantly more prevalent than in 2015. Furthermore, students who had received sex and STI/HIV prevention education and rated it as "good" (OR = 5.62, 95% CI: 2.72–11.64), who believed they could confidently refuse sex without a condom(OR = 1.95, 95% CI: 1.14–3.32), and who reported consistent condom use(OR = 2.27, 95% CI: 1.21–4.25) were also more prevalent in 2021. Use of contraception methods such as condoms(OR = 2.76, 95% CI: 1.50–5.09), the pill(OR = 2.42, 95% CI: 1.35–4.35), extracorporeal ejaculation (OR = 1.77, 95% CI:1.02–3.09), and the safe period(OR = 2.22, 95% CI: 1.22–4.04) also increased significantly. However, the proportion of students who had their first sexual relationship with a non-regular partner decreased(OR = 0.47, 95% CI: 0.24–0.93).ConclusionThe participants' knowledge of safe sex and sexual behaviour improveed between the two surveys. However, these positive changes have not had a significant enough impact to prevent STIs/HIV transmission and reduce pregnancy. Further efforts are needed to ensure that these changes lead to effective STIs/HIV prevention and reduction among students.